“It was a man’s name but a woman’s body”: the transexual population in the family health strategy - Spadim, Bárbara Cristina de Léo [UNESP]; Mendonça, Carolina Siqueira [UNESP]; Cyrino, Eliana Goldfarb [UNESP] (FapUNIFESP (SciELO), 2024)
Despite the creation of policies that seek to promote equality for transexuals, an alarming reality exists characterized by a high level of vulnerability. When seeking health care, transexuals have experiences that create barriers to access. The aim of this study was to analyze the health care challenges for this group in family health strategy services in the municipality of São Paulo, characterizing the representations of professionals, availability of care and training. We conducted an exploratory study using a qualitative design based on semi-structured interviews. The data were analyzed using content analysis as proposed by Minayo and descriptive statistics, resulting in the following units of analysis: demand exists; the training void; and echoes of violence. The interviewees’ accounts point to stigma, lack of public policy, prejudice and violence against transexuals.
“El nombre era de hombre, pero era un cuerpo de mujer”: la población transexual en la estrategia de la salud de la familia
“O nome era de homem, mas era um corpo de mulher”: a população transexual na Estratégia Saúde da Família
Keywords: Health education; Qualitative research; Transexual; Vulnerability